1999
DOI: 10.1029/1999gl900435
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear two‐stream instabilities as an explanation for auroral bipolar wave structures

Abstract: Abstract.The evolution of two counter-streaming electron beams is shown by means of 2-D kinetic simulations to lead to electron distributions and coherent localized bipolar plasma wave structures with features similar to those measured by the FAST satellite in the auroral ionosphere. Electrostatic whistler waves are generated at later times when the bipolar structures begin to lose coherence and break up in the dimension transverse to the geomagnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(169 citation statements)
references
References 13 publications
13
154
0
Order By: Relevance
“…[35,36]), and ES whistler waves have been shown to be responsible for decay of electron holes formed in simulations of beam-plasma systems [37,38]. In VTF it was found that during reconnection events where holes were not observed, there was nonetheless still substantial electrostatic turbulence in this same frequency range f LH < f < f ce [23], termed "lower-hybrid" modes since the frequency spectrum peaked at a few times f LH .…”
Section: Electrostatic Vs Electromagnetic Responsementioning
confidence: 96%
“…[35,36]), and ES whistler waves have been shown to be responsible for decay of electron holes formed in simulations of beam-plasma systems [37,38]. In VTF it was found that during reconnection events where holes were not observed, there was nonetheless still substantial electrostatic turbulence in this same frequency range f LH < f < f ce [23], termed "lower-hybrid" modes since the frequency spectrum peaked at a few times f LH .…”
Section: Electrostatic Vs Electromagnetic Responsementioning
confidence: 96%
“…Although there is no simple explicit expression for n p (φ) that can be obtained with the distribution (17), one can use an expansion for small φ to analyse the behaviour of the passing electrons (Krasovsky et al, 1997),…”
Section: Passing Electronsmentioning
confidence: 99%
“…The negative potential ESWs have been interpreted in terms of ion solitary waves or solitons (Koskinen et al,904 G. S. Lakhina et al: Study of nonlinear ion-and electron-acoustic waves been commonly interpreted in terms of as Bernstein-GreeneKruskal (BGK) modes (Bernstein et al, 1957;Muschietti et al, 1999;Jovanovic and Shukla, 2000;Chen et al, 2005). Other favorite interpretations for these ESWs are based on the nonlinear evolution of a bump-on-tail instability/electron two stream instability (Omura et al, 1996;Kojima et al, 1997;Goldman et al, 1999), and electron-acoustic solitary waves (Pottelette et al, 1990;Dubouloz et al, 1991Dubouloz et al, , 1993Lakhina, 2001, 2004;Tagare et al, 2004. For a detailed discussion of various models, one can refer to Lakhina et al (2000Lakhina et al ( , 2004.…”
Section: Introductionmentioning
confidence: 99%